Extraction of Spatial Distribution Characteristics of Jiangnan Urban Landscape under the Influence of Geomorphology - Shuhua Wang; Anhua Qin (Complexity)
This paper presents an in-depth study and analysis of the spatial distribution of urban landscapes in Jiangnan cities under the influence of geomorphology and extracts the characteristics to explore the construction mechanism from the perspective of spatial functionality based on the analysis of the process and content of landscape construction. The construction of cities and ponds originated from political influence, environmental constraints, and architectural techniques; the landscape pattern of the combined shape and complementary potential originated from the creation of various types of gardens in various dynasties; the complementary planning of landscape, the traffic creation of the plain and water network, and the production factors of agriculture and sanitation influenced the construction of the countryside landscape; the traditional view of feng shui, poetry and painting, the eight scenes of the city and countryside, and other humanistic intentions influenced the overall situation of the town and the landscape. This paper extracts and analyzes the spatial distribution characteristics of Jiangnan city landscape from several perspectives, and the results can clearly show the distribution of landscape features under the influence of geomorphology and can give the best layout suggestions. From the perspective of spatial variability, the main features of traditional landscape construction in Jiangnan are analyzed through three levels: the characteristics of the process of humanized landscapes evolving into natural landscapes, the comparative analysis of similarities and differences in the construction of cities and towns, and the characteristics of the system of regional landscape construction. Finally, the changes in the landscape pattern of the region under the influence of globalization are analyzed through the changing characteristics of landscape architecture.